A Patient’s Journey with DiGeorge Syndrome: Navigating Diagnostic and Treatment Challenges - Amoasii, Dumitru (Medical Science: Trends and Innovations Vol. 7, 2025)
Background: DiGeorge syndrome (also known as velo-cardio-facial syndrome) is a rare genetic condition affecting about 1 in 4,000 to 6,000 live births. While advancements in genetic testing have improved early diagnosis in developed countries, it remains underrecognized in places like Moldova, where access to these tests is limited. Prenatal screening usually includes ultrasounds and routine checks, but the syndrome is hard to detect through ultrasound alone, especially since it often doesn’t show up in clear ways during pregnancy. Genetic testing is usually done when doctors suspect a genetic issue, but this can be missed or delayed, especially when the signs are subtle. Purpose: This study aims to shed light on the diagnostic challenges of DiGeorge syndrome, urging doctors to think about it as a multi-faceted condition, rather than focusing on just one system or symptom at a time. Method: This study presents the case of a 6-month-old girl, born after an uneventful pregnancy and with a normal prenatal ultrasound, who started showing signs of heart failure. After a series of tests and surgeries, she was eventually diagnosed with DiGeorge syndrome at 9 months. Results: The diagnosis was delayed because there were no clear prenatal markers, and doctors focused on investigating her heart and other individual issues rather than looking at the bigger picture. Despite several treatments to manage her symptoms, the diagnosis was only made after noticing the pattern of various symptoms and conducting genetic tests.